Maltol prevents the progression of osteoarthritis by targeting PI3K/Akt/NF‐κB pathway: In vitro and in vivo studies. Issue 1 (19th November 2020) - Lu, Hongwei; Fu, Changchang; Kong, Suyan; Wang, Xudong; Sun, Lin; Lin, Zeng; Luo, Peng; Jin, Haidong
Abstract: Osteoarthritis (OA), a prevalent degenerative arthritis disease, principle characterized by the destruction of cartilage and associated with the inflammatory response. Maltol, a product formed during the processing of red ginseng (Panax ginseng, CA Meyer), has been reported to have the potential effect of anti‐inflammatory. However, its specific mechanisms are not demonstrated. We investigated the protective effect of maltol in the progression of OA both in vitro and in vivo experiments. Human chondrocytes were pre‐treated with maltol (0, 20, 40, 60 μM, 24 hours) and incubated with IL‐1β (10 ng/mL, 24 hours) in vitro. Expression of PGE2, TNF‐α and NO was measured by the ELISA and Griess reaction. The expression of iNOs, COX‐2, aggrecan, ADAMTS‐5, MMP‐13, IκB‐α, p65, P‐AKT, AKT, PI3K and P‐PI3K was analysed by Western blotting. The expression of collagen II and p65‐active protein was detected by immunofluorescence. Moreover, the serious level of OA was evaluated by histological analysis in vivo. We identified that maltol could suppress the IL‐1β‐stimulated generation of PGE2 and NO. Besides, maltol not only suppressed the production of COX‐2, iNOs, TNF‐α, IL‐6, ADAMTS‐5, MMP‐13, but also attenuated the degradation of collagen II and aggrecan. Furthermore, maltol remarkably suppressed the phosphorylation of PI3K/AKT and NF‐κB induced by IL‐1β in human OA chondrocytes. Moreover, maltol could block the cartilage destroy in OA mice in vivo. To date, all data indicate maltol is a potential therapeutic agent by inhibiting inflammatory response via the regulation of NF‐κB signalling for OA.